Health Education About Clean and Healthy Lifestyle Behavior (PHBS) in the Transition Period of the Covid-19 Pandemic for Students - Debie Rizqoh; Ellen Maidia Djatmiko; Nikki Aldi Massardi; Alvi Jalilul Hakim; Novita Arifani; Azella Chika Fauzia (CV Media Inti Teknologi, 2023)
After the COVID-19 pandemic is ongoing up to 3 years, finally Indonesia started experience transition from pandemic going to endemic, following decreasing of case positive for COVID-19. During the transition, a number of rule start relaxed, however government recommend public for still carry out health protocol. Besides, in field education, all school carry out 100 % offline learning. The students have to stay alert from COVID-19 infection or another infection. So that, clean and healthy lifestyle (PHBS) is necessary carried out at school. There are several indicators of PHBS in schools that are necessary known by students. This health education aims to give education to 97 students in schools especially at SMK Negeri 2 Bengkulu City about importance implementing PHBS in the transition period of COVID-19 pandemic. This activity took place on Thursday , 22 September 2022. The method used form give education and discussion regarding PHBS in schools. We evaluated student’s understanding by pre-test and post-test about PHBS. Participant generally already have own knowledge regarding PHBS and more understand PHBS after participated in this activity.